'Football fans are not thugs': communication and the future of fan engagement in the policing of Scottish football. (21st April 2022) - Atkinson, Colin
ABSTRACT: The recent history of the policing of Scottish football has been tempestuous. The enactment of the Offensive Behaviour at Football and Threatening Communications (Scotland) Act 2012 subjected those attending regulated football matches to a range of new forms of control, and mobilised significant fan resistance that resulted in the Act's eventual repeal in 2018. By this time, however, significant damage had been inflicted upon fan-police relations, with a concomitant impact on communication and fan engagement. Drawing upon the findings of qualitative research conducted in Scotland, the analysis herein documents a recognition on all sides of the poor state of fan-police relations following the implementation of the original Act. This research traces an emergent shift in some policing sensibilities towards more constructive forms of police-fan engagement and communication following the Act's repeal. However, the study also highlights significant challenges to such emergent sensibilities, acknowledging, via a case study, that they exist in parallel with still highly problematic practices and approaches in the policing of football fans in Scotland.